2020
DOI: 10.1039/d0nh00340a
|View full text |Cite
|
Sign up to set email alerts
|

The oxygen vacancy in Li-ion battery cathode materials

Abstract: The substantial capacity gap between available anode and cathode materials for commercial Li-ion batteries (LiBs) remains, as of today, an unsolved problem. Oxygen vacancies (OVs) can promote Li-ion diffusion, reduce...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
75
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 102 publications
3
75
0
Order By: Relevance
“…The rational and controllable introduction of defects can adjust the key physicochemical properties of materials, including but not limited to electronic structure, geometric configuration, and surface adsorption. [ 14,15 ] For example, Zhang et al. [ 16 ] reported the fabrication of oxygen‐deficient MoO 3‐x ‐based anode via solution reduction method.…”
Section: Introductionmentioning
confidence: 99%
“…The rational and controllable introduction of defects can adjust the key physicochemical properties of materials, including but not limited to electronic structure, geometric configuration, and surface adsorption. [ 14,15 ] For example, Zhang et al. [ 16 ] reported the fabrication of oxygen‐deficient MoO 3‐x ‐based anode via solution reduction method.…”
Section: Introductionmentioning
confidence: 99%
“…These limited studies suggest that the introduction of oxygen vacancies can improve electrical conductivity and increase active site, which is beneficial to enhancing lithium storage remarkably [28][29][30][31]. For example, Qiu and co-workers [32,33] obtained oxygen-deficient TiO 2 with a capacity of 128 mA h g −1 at 5 C when used as the anode in LIBs. Li et al [34] synthesized oxygen-vacancy-abundant ZnCo 2 O 4 for LIBs and found that it exhibited an excellent capacity of 746 mA h g −1 at 1 C. However, the effect of oxygen vacancies in TMOs remains ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…The app is free and open-source and it is available for download on Github 12 . We have also built a TEM ImageNet project website for searching, browsing, and downloading of the training images and labels 13 .…”
Section: Introductionmentioning
confidence: 99%
“…AtomSegNet is intended to become a pre-processing module of a complete TEM image processing workflow that include extensions of materials and zone axis recognition, crystal phase mapping, dislocation and defect detection, atomic counting, strain mapping, etc. The training data sets and labels are available for download, searching and browsing at the project website 13 .…”
Section: Introductionmentioning
confidence: 99%